Hybrid Gibbsite Nanoplatelet/Cellulose Nanocrystal Multilayered Coatings for Oxygen Barrier Improvement - Chemin, Maud; Heux, Laurent; Guérin, David; Crowther-Alwyn, Laura; Jean, Bruno (Frontiers in Chemistry, 2019)
The potential of multilayered cellulose nanocrystals (CNCs)/gibbsite nanoplatelets (GNPs) thin films to be built onto various substrates of interest for packaging applications using the layer-by-layer assembly and to improve their oxygen barrier properties has been explored. First, the use of complementary structural characterization techniques, namely AFM, ellipsometry and spectral reflectance, evidenced that when deposited onto model silicon substrates the all-nanoparticles hybrid films were homogenous, of very reduced porosity, and exhibited a thickness linearly increasing with the number of deposited layers, which is fully compatible with the alternating deposition of monolayers of GNPs and of CNCs. Secondly, scanning electron microscopy observations showed the successful deposition of such homogeneous and dense hybrid thin films onto various types of flexible substrates such as cardboard, blotting paper, smart paper, polyethylene (PE) films, PE-coated cardboard, which display very different chemical compositions, hydrophilicities, and surface morphologies. These results show the remarkable robustness of the deposition and building process, which is likely due to the versatility of the LbL assembly technique and to the strong electrostatic and hydrogen bonding interactions between the two types of colloids. The measurement of the oxygen transmission rate at 23°C and 50% RH showed that the oxygen barrier properties of the bare substrates could be significantly improved (e.g. 75% decrease of the OTR) after the deposition of such thin (<100 nm) hybrid multilayer films. This enhancement was attributed to the strong increase in tortuosity related to the very low porosity of the films, which impedes gas diffusion. This proof of concept paves the way to the use of these partially biosourced ultrathin films as coatings with high oxygen barrier performance.